The Emergence of Modern Municipalism in the Ottoman Empire and the First Municipal Activities in Safranbolu - Bilirli, Tahir (Journal of History Culture and Art Research, 2021)
In this study, the transformation of municipal services, which were tried to be carried out by some traditional institutions such as “vakif” and “lonca”, or by “kadi” who was the higher governor in the administration of the city until the 19th century in the Ottoman Empire, into a modern municipality understanding as a result of changing conditions and necessities was examined. In the introduction part of the study, after examining the traditional municipal practices of the Ottoman Empire until the mid-19th century, the transition process to modern municipality in the 19th century was studied. In the first part of the research, the municipal services traditionally carried out by kadi, naip, lonca and vakif from the establishment of the Ottoman Empire to the abolition of the Janissary Corps in 1826 were discussed. In the second part, the transition process from traditional municipality to modern municipality was evaluated. With the effect of internal and external dynamics, the necessity of performing municipal services in a more organized manner from a single center has been demonstrated with examples. In the third part, the contributions of municipalities to the development and development of the city, municipal services carried out to increase the quality of life of its people, and by whom the services are carried out since the establishment of Municipality of Safranbolu in 1870 was evaluated. In addition, the transition stages from the unorganized structure of municipalities formed during the service delivery phase to the institutionalization of them were scrutinized. The importance of the municipality in the establishment of the military regiments that played a leading role in the development of the cities in Safranbolu, in the construction of inner-city sidewalks and roads and the connection roads with other cities were underlined. In addition, it has been determined that municipalities have started to take a role in social solidarity and organization issues, as in the protest rallies held during the occupation of the country after the First World War.